THE INFLUENCE OF ISLAMIC NURSING IN NURSE’S JOB SATISFACTION - Sudalhar, Sudalhar (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2017)
Job satisfaction in nurses who apply Islamic nursing cannot be explained. This could caused nursing services based on positivism and pragmatism, which keeeping nurses away from universal ethical values, so that nursing care will not deliver asense of love and compassion to the other creatures created by Allah because the only motivation is only for short-term purpose, such as just for fulfilling obligation and for salary. This study aimed to prove the influence of Islamic nursing on job satisfaction in nurses of Bojonegoro Aisiyah Hospital. This research was conducted in 34 respondents who were permanent nurses in Bojonegoro Aisiyah Hospital, with one group pre-post test design. It done in April 7th to June 7th 2011. The population was all permanent nurses in Bojonegoro Aisiyah Hospital whom deal directly to the clients. The Independent variable was Islamic nursing aplication, and dependent variable was nurse job satisfaction. In this study, measurement nurse?s job satisfaction using 19 questions to identify nurse?s job satisfaction before and after apply Islamic nursing, then data were analyzed with wilcoxon test in significan level ? 0,05.The Result showed ? = 0,014<0,05, indicating there was influence of the implementation of Islamic nursing on nurses?s job satisfaction, in the aspects of job content, remuneration, promotion, working condition, coworkers, and supervision at the Bojonegoro Aisiyah Hospital so research hipotesis accepted.The nurses in Bojonegoro Aisiyah Hospital should to improve implementation religious correctly to raise spirituality among the nurse themselves, and increase the application of Islamic nursing, with the following indicators: professionals, friendly, istiqomah, trustworthy and sincere in nursing services in order to achievethe vision of Bojonegor Aisiyah Hospital tobecome professional, hospital of choice, and Islamic in 2015. The next research about client satisfaction in Islamic nursing is needed too